2020
DOI: 10.1212/wnl.0000000000008738
|View full text |Cite
|
Sign up to set email alerts
|

Homonymous hemiatrophy of ganglion cell layer from retrochiasmal lesions in the visual pathway

Abstract: ObjectiveTo determine the temporal evolution, morphology, and frequency of macular ganglion cell atrophy in patients with retrochiasmal lesions of the visual pathway.MethodsIn a consecutive retrospective case series, we identified 47 patients with homonymous hemianopia and accessible macular optical coherence tomography scans. We estimated the time of lesion onset and the location of the lesion within the afferent visual pathway. Using semiautomatic layer segmentation, we determined ganglion cell layer thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Optical coherence tomography (OCT) is widely deployed in ophthalmology to quantify and monitor optic neuropathies, most frequently via the peripapillary nerve fiber layer (pRNFL). It has recently been shown that adding the macular ganglion cell layer (mGCL) thickness may have a better sensitivity than pRNFL alone in detecting optic neuropathies, and that the distribution of mGCL loss may provide additional localizing value of optic neuropathies [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is widely deployed in ophthalmology to quantify and monitor optic neuropathies, most frequently via the peripapillary nerve fiber layer (pRNFL). It has recently been shown that adding the macular ganglion cell layer (mGCL) thickness may have a better sensitivity than pRNFL alone in detecting optic neuropathies, and that the distribution of mGCL loss may provide additional localizing value of optic neuropathies [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…6). Homonymous hemiatrophy of the ganglion cell layer was recently reported in a retrospective series of 47 patients with HVFD of various aetiologies [49]. The authors reported that such homonymous hemiatrophy could result from either direct retrograde axonal degeneration or transsynaptic retrograde axonal degeneration.…”
Section: Discussionmentioning
confidence: 90%
“…The characteristic homonymous GCIPL thinning detected by OCT corresponds to ipsilateral occipital lesions and to contralateral homonymous quadrant‐ or hemianopia. This pattern of GCIPL thinning could be considered as direct evidence of retrograde degeneration and has been found in both congenital and acquired damages of the retrochiasmal pathway (Foster et al., 2019 ; Huang‐Link et al., 2014 ; Keller et al., 2014 ; Mühlemann et al., 2020 ; Yamashita et al., 2016 ). In our study, those with NVFD showed no homonymous GCIPL thinning and the average GCIPL thickness was relatively intact.…”
Section: Discussionmentioning
confidence: 91%